EEGNet classification of sleep EEG for individual specialization based on data augmentation - Xia, Mo; Zhao, Xuyang; Deng, Rui; Lu, Zheng; Cao, Jianting (Cognitive neurodynamics, 2024)
Sleep is an essential part of human life, and the quality of one’s sleep is also an important indicator of one’s health. Analyzing the Electroencephalogram (EEG) signals of a person during sleep makes it possible to understand the sleep status and give relevant rest or medical advice. In this paper, a decent amount of artificial data generated with a data augmentation method based on Discrete Cosine Transform from a small amount of real experimental data of a specific individual is introduced. A classification model with an accuracy of 92.85% has been obtained. By mixing the data augmentation with the public database and training with the EEGNet, we obtained a classification model with significantly higher accuracy for the specific individual. The experiments have demonstrated that we can circumvent the subject-independent problem in sleep EEG in this way and use only a small amount of labeled data to customize a dedicated classification model with high accuracy.